Cultural Integration and Collaborative Pedagogy in Qur’anic Literacy: The Tahsin Program's Innovative Model - Sri Nurhayati; Eva Vitariani; Taufikin Taufikin (STAI Hubbulwathan Duri, 2025)
This study explores the transformative impact of the Tahsin Program on advancing Qur’anic literacy by integrating culturally responsive pedagogy with contextually grounded instructional design. Addressing the gap in inclusive, community-rooted religious education, the program aims to foster both linguistic proficiency and cultural identity. A qualitative case study approach was employed at a community-based learning center in Cimahi, Indonesia. Data were gathered through semi-structured interviews, focus group discussions, direct classroom observations, and document analysis. This multi-method strategy ensured a comprehensive understanding of the program’s design and outcomes. Findings revealed that over 80% of learners improved their Tajweed proficiency within three months. The program’s unique integration of modular curriculum progression, localized content, intergenerational mentorship, and embedded formative feedback contributed significantly to learner success. Culturally embedded practices—particularly the inclusion of elders—enhanced communal learning and reinforced cultural identity. Peer mentoring and dialogic group discussions fostered interpretive depth and active engagement, while ongoing feedback supported differentiated instruction and learner autonomy. The Tahsin Program exemplifies how pedagogical models that blend tradition with innovation can enhance religious education. By grounding the curriculum in social constructivist theory, the program accommodates diverse learner profiles and promotes sustainable community involvement. This study highlights the effectiveness of context-sensitive, culturally grounded Qur’anic education. Future research should explore how digital tools can scale such models for broader urban and online application.